Practical Guide Based on Learning Cycle 5E to Enhance Students’ Cognitive Learning Outcomes - Pangestika, Dwi Safriani; Prasetyo, Zuhdan Kun (Biosaintifika: Journal of Biology & Biology Education, 2018)
The practical guide is a teaching material that students use in labwork activities. This learning cycle 5E (Engangement, Exploration, Explanation, Elaboration, Evaluation) on practical guide is expected to be used as an alternative choice for teacher in improving students’ cognitive learning outcomes in concept of pressure and symptoms of capillarity in plants. The aim of this study was : 1) to describe the feasibility of develop practical guide based on learning cycle 5E and 2) to analyse the improvement of the practical guide based on learning cycle 5E to enhance cognitive learning outcomes of eight graders of junior high school in science lesson. Here, we used the Research and Development refers to the procedural steps of the 4D models by Thiagarajan. To test the efficacy, pretest and posttest were employed.This is a quasi-experiment research conducted in MTsN 3 Ngawi. Research subjects were all students of grade 8 by taking class 8A as the experimental class and 8B as the control class. Samples were taken by cluster sampling technique. The result of the feasibility test showed that practical guide included in the excellent category. T-test analysis suggests that the practical guide based on learning cycle 5E could improve students’ cognitive learning outcomes significantly. In addition to contributing to the improvement of students’ cognitive learning outcomes in MTsn 3 ngawi, the development of science cycle-based learning guide based on learning cycle 5e can also provide students practice skills in learning so that it is expected to contribute posotif in the community.